Analisis Kapasitas Fiskal Daerah: Studi Kasus di Kabupaten Gunung Kidul - Sriyana, Jaka (Unisia, 2012)
Intergovernmental fiscal transfers are critical elements of public finance in decentralized countries. In the context of Indonesia’s decentralization reforms, their design and implementation have significant impacts on the potential revenue and fiscal capacity of basic public service provision. The case of Indonesia’s 2001 Big Bang decentralization illustrates the challenges associated with implementing significant reforms in the intergovernmental fiscal system. The practice of decentralization policy in Indonesia since the time has not generally improved local development performance yet. This study evaluates fiscal decentralization, focusing on fiscal capacity as the impacts of the intergovernmental fiscal equalization transfers, in the case of Gunung Kidul, Yogyakarta. The study shows a low percentage of its own revenue compared to its total budget. It indicates the failure of fiscal decentralization policy in improving local government fiscal capacity.